On the general concept of bribery crime: The rationale for the need of its introduction into scientific nomenclature - E.V. Fomenko (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper analyzes the need to identify the general concept of bribery crime in the Russian Federation. The origin of this concept has been studied using the dialectical research methods, in particular the ascent from the abstract to the concrete in thinking. The problem of the general concept of bribery crime is relevant because of its theoretical and practical significance. It is necessary to carry out the separation from the total mass and further systematization in the unifying concept of the whole set of homogeneous features inherent in the acts of this group of crimes. The definition of this concept is intended to ensure the completeness and diversity of the perception of all elements and signs of specific elements of crimes related to bribery, to eliminate the existing legislative problems and gaps, as well as to form a basis for the impeccable qualification of this group of crimes in the current criminal legislation of the Russian Federation. The purpose of the research is to study and analyze of the elements and signs of crimes related to bribery in their relationship and interdependence. It lies in the argumentative-doctrinal basis for identification of the general concept of elements of crimes associated with bribery and corresponds to the attempt undertaken in this work to disclose and analyze the signs and elements of the general concept of elements of the designated illegal criminal act.